2022
DOI: 10.17146/aij.2022.1180
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Electron Contamination on Flattened and Unflattened Varian Clinac iX 6X and 15X Photon Beam Based on Monte Carlo Simulation

Abstract: The aim of this study was to characterize electron contamination of a flattened (FF) and an unflattened (FFF) Varian Clinac iX 6X and 15X photon beams using Monte Carlo (MC) simulation. EGSnrc MC technique was used to model the flattened and unflattened head and simulate dose distribution of 6X and 15X of FF and FFF photon beam in water phantom. The materials and geometrical data of FF linac were provided by Tan Tock Seng Hospital (TTSH) Singapore. The FFF linac was modeled by removing the flattening filter co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It serves as an absorber of secondary electrons generated from the upper components of LINAC's head and prevents them from reaching the patient's body surface; however, it is the primary source of secondary electrons that reach the build-up region [2,38]. Contaminant electrons significantly contributed to the increasing surface dose by removing the flattening filter [5,39,40]. Mesbahi et al (2009) reported that removing the flattening filter leads to a notable increase in the fluence of contaminant electrons up to 1.6 times, which has caused increasing radiation dose delivered to the patient's skin [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It serves as an absorber of secondary electrons generated from the upper components of LINAC's head and prevents them from reaching the patient's body surface; however, it is the primary source of secondary electrons that reach the build-up region [2,38]. Contaminant electrons significantly contributed to the increasing surface dose by removing the flattening filter [5,39,40]. Mesbahi et al (2009) reported that removing the flattening filter leads to a notable increase in the fluence of contaminant electrons up to 1.6 times, which has caused increasing radiation dose delivered to the patient's skin [41].…”
Section: Discussionmentioning
confidence: 99%
“…The FF commonly comprises high atomic number materials, such as copper (Cu). In modern treatment techniques, which require high-energy photon beams, homogeneous beams are not necessary, as seen in stereotactic body radiation therapy (SBRT), intensity-modulated radiation therapy (IMRT), and LINAC-based radiosurgery [5]. Several studies have reported the concept of freeflattening filter (FFF) beams at various energies [6,7].…”
Section: Introductionmentioning
confidence: 99%